High blood pressure and associated risk factors as indicator of preclinical hypertension in rural West Africa: A focus on children and adolescents in The Gambia. Issue 13 (March 2017) - Jobe, Modou; Agbla, Schadrac C.; Prentice, Andrew M.; Hennig, Branwen J.
Abstract : Abstract: Hypertension is fast becoming a major public health problem across sub-Saharan Africa. We sought to determine the prevalence of high blood pressure (BP) and associated risk factors as indicator of preclinical hypertension in a rural Gambian population. We analyzed data on 6160 healthy Gambians cross-sectionally. Attention was given to 5 to <18-year olds (N = 3637), as data from sub-Saharan Africa on this young age group are scarce. High BP was defined as systolic blood pressure (SBP) above the 95th percentile for age-sex specific height z scores in <18-year olds employing population-specific reference values. Standard high BP categories were applied to ≥18-year olds. In <18-year olds, the multivariable analysis gave an adjusted high BP prevalence ratio of 0.95 (95% confidence interval [CI] 0.92–0.98; P = 0.002) for age and 1.13 (95% CI 1.06–1.19; P < 0.0001) for weight-for-height z score (zWT-HT); sex and hemoglobin were not shown to affect high BP. In adults age 1.05 (95% CI 1.04–1.05; P < 0.0001), body mass index z score 1.28 (95% CI 1.16–1.40; P < 0.0001), hemoglobin 0.90 (95% CI 0.85–0.96; P < 0.0001) and high fasting glucose 2.60 (95% CI 2.02–3.36; P < 0.0001, though the number was very low) were confirmed as risk factors for high BP prevalence; sex was not associated. The reported high BP prevalence and associated risk factors in adults are comparable to other studies conducted in the region. The observed high BP prevalence of 8.2% (95% CI 7.4–9.2) in our generally lean young Gambians (<18 years) is alarming, given that high BP tracks from childhood to adulthood. Hence there is an urgent need for further investigation into risk factors of pediatric high BP/hypertension even in rural African settings. Abstract : Supplemental Digital Content is available in the text